Role of panchayat secretary in Andhra Pradesh - A study - Kumar, A. Vijay; Sudhakar, E. (2003)
The third-tier structure in decentralised three-tier system of panchayati raj governance in Andhra Pradesh has received some bureaucratic modifications with the introduction of Panchayat Secretariat system with Panchayat Secretary as its head. In this context the present study reviews its performance and the way of functioning of this newly created institution. Based on the responses of panchayats, secretaries of Panchayat Secretariat, political executives of panchayat raj system and people of the rural areas, the paper examines the problems as well as the role of panchayat secretaries in village secretariat in discharging their duties and responsibilities. - Reproduced.
Keywords: Panchayat - India - Andhra Pradesh; Panchayat